The Influence of Organizational Learning and Job Characteristic on Organizational Commitment and Employee Performance of Clinical Laboratory, type B Regional General Hospital in East Java - santoso, didik agus (Archives of Business Research, 2018)
This study aimed to investigate the influence of organizational learning and job characteristic on organizational commitment and employee performance of Clinical laboratory, type B Regional General Hospital in East Java. This study is a causal explanatory research. The populations are 300 employees and using simple random sampling, 220 respondents were selected. The analysis data with the Structural Equation Modeling (SEM). Organizational learning has significant influence on organizational commitment; organizational learning has significant influence on employee performance, job characteristic has significant influence to organizational commitment, job characteristic has significant influence to employee performance. and organizational commitment has no significant influence on employee performance of Clinical laboratory, type B Regional General Hospital in East Java. The results of this study indicate that our of five hypotheses were accepted, namely: organizational learning and job characteristic organizational commitment; organizational commitment and job characteristic on employee performance.